2018
DOI: 10.1891/1058-1243.27.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Childbirth and Its Aftermath: Is There Anything Positive?

Abstract: Up to 45% of new mothers have reported experiencing birth trauma. For some individuals who have experienced a traumatic event, there can be a positive legacy called posttraumatic growth. Using Tedeschi and Calhoun’s Posttraumatic Growth Model as the theoretical framework, the purpose of this pilot study was to determine levels of posttraumatic stress, core beliefs disruption, and posttraumatic growth in women who have experienced traumatic childbirth. Thirty mothers completed the Posttraumatic Stress Disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The present study showed a low level of PTG in women after childbirth, which was similar to the finding of a study involving mothers from five countries who experienced a traumatic birth, but lower than that in another study involving mothers from Europe 36 months after childbirth. 17,37 The results also indicated that the participants exhibited the greatest growth in their appreciation of life, which is consistent with the findings of Sawyer's study, 17,18 and the lowest growth in new possibilities, which contrasts with the findings of other studies. 16,18 This result suggested that after giving birth, women had a profound understanding of the value of life and parenting in general, which may increase their perception of life, but the participants had less positive growth in being aware of or trying new possibilities.…”
Section: Ptg In Women After Childbirthsupporting
confidence: 82%
“…The present study showed a low level of PTG in women after childbirth, which was similar to the finding of a study involving mothers from five countries who experienced a traumatic birth, but lower than that in another study involving mothers from Europe 36 months after childbirth. 17,37 The results also indicated that the participants exhibited the greatest growth in their appreciation of life, which is consistent with the findings of Sawyer's study, 17,18 and the lowest growth in new possibilities, which contrasts with the findings of other studies. 16,18 This result suggested that after giving birth, women had a profound understanding of the value of life and parenting in general, which may increase their perception of life, but the participants had less positive growth in being aware of or trying new possibilities.…”
Section: Ptg In Women After Childbirthsupporting
confidence: 82%
“…Try asking open-ended questions to get more information about what women might be saying (Hayden, 2022). Beck and Watson (2016) and Beck et al (2018) recommend that healthcare professionals be wary of the metaphors women use to help describe their experiences of post-traumatic stress. In addition, at infants' well-baby checkups and yearly physical exams, healthcare professionals are recommended to ask mothers how they are doing and how they evaluate their birth experiences (Beck, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, healthcare professionals may play an important role in facilitating this by encouraging mothers to explore their faith and use their social support networks, and informing mothers about organizations and resources that provide niche support after traumatic birth (Brown et al, 2022). In addition, healthcare professionals can provide some hope to women who have experienced psychological birth trauma by sharing the possibility of post-traumatic growth (Beck and Watson, 2016;Beck et al, 2018). Notably, the possibility of positive effects does not diminish the importance of preventing psychological birth trauma (Ketley et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy during the pandemic is a stressful life event. Studies report that posttraumatic growth (PTG), which is the positive psychological change resulting from challenging life events or circumstances [ 28 ], may occur in people after a stressful life event [ 29 , 30 , 31 , 32 , 33 ]. Studies regarding PTG in perinatal women focused mainly on childbirth and adverse pregnancy outcomes, including preterm births and pregnancy loss [ 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%